A Sin in the Convent - Akadiri, Oladele (Heinemann Educational Books Nig. Ltd, 1990)
When the unsuspecting Ignatius Okafor stops to give attractive Mary Smith a ride in his car, he unknowingly sets off a chain of events which lead to very tragic consequences. The naïve Ignatius, the beautiful Mary and rowdy Barrister John ends up in a complicated menage a trois...
Keywords: Juvenile Fiction